1996
DOI: 10.1111/j.1398-9995.1996.tb00021.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of total serum IgE and specific IgE to common aeroallergens by sex and age, and their relationship to each other in a random sample of the Dutch general population aged 20–70 years*

Abstract: To describe the distribution of serum total IgE and specific IgE. to common aeroallergens by sex and age and to study their relationship to each other, we measured serum total IgE and specific IgE (CAP) to house-dust mite, timothy grass, cat, birch, and Cladosporium in a random sample of 2496 subjects, aged 20-70 years from the Dutch general population. We found that total IgE was higher in men, independently of smoking, and that total IgE had no relationship with age after adjustment for specific IgE and smok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
41
2
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 13 publications
8
41
2
2
Order By: Relevance
“…Our results corroborate previous observations that showed a positive relationship between active smoking and total serum IgE levels [3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15]. It is possible that persons with any allergic disorder are more likely not to start smoking or to quit smoking if they do smoke and that those without such symptoms are likely to go on smoking (healthy smoker effect).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our results corroborate previous observations that showed a positive relationship between active smoking and total serum IgE levels [3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15]. It is possible that persons with any allergic disorder are more likely not to start smoking or to quit smoking if they do smoke and that those without such symptoms are likely to go on smoking (healthy smoker effect).…”
Section: Discussionsupporting
confidence: 82%
“…A number of epidemiological studies have showed that cigarette smoking is associated with elevated concentrations of total serum IgE [3, 4, 5, 6, 7, 8, 9, 10], even after adjustment for age and sex [11, 12, 13, 14, 15]. Also, there have been some studies that investigated the relationship between exposure to environmental tobacco smoke (ETS) and total serum IgE in adults.…”
Section: Introductionmentioning
confidence: 99%
“…The decline is similar to studies carried out in the age groups of 20–70 years which found a decline in mite IgE with increasing age [53]. …”
Section: Discussionsupporting
confidence: 73%
“…A higher prevalence of allergies in males, when described by mite IgE [53, 54] or by mite SPT [55, 56,] has been described in several studies in Europe. The absence of a gender-related difference in mite SPT has been observed in other studies conducted in developing countries [8, 30] and the mechanisms behind this discrepancy in the data generated in western populations and those in developing countries have not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of being overweight or obese in patients with chronic kidney diseaseundergoing hemodialysis are paradoxicallyin the opposite direction. This phenomenon has been referred to as ‘reverse epidemiology’ [44]. Among PD patients the amount of glucose absorbed from the dialysis solution makes caloric malnutrition unusual.…”
Section: Discussionmentioning
confidence: 99%